Impact of knowledge management, innovation and cloud computing on research - Adil Hayat; Jianhua Zhang; Ajaz Sadiq; Nibah Begum (Information Technology and Science (ITScience), 2023)
This Review article delves into the intricate relationship between knowledge management, innovation, and cloud computing, and their transformative impact on research across diverse fields. Drawing upon a wide range of literature, the article critically assesses the potential of these technologies in reshaping the landscape of scientific research, social science research, business and management, and education. The review highlights key insights and findings that showcase the immense possibilities of cloud-based solutions in revolutionizing research practices, including real-time data sharing, enhanced collaboration, and seamless access to cutting-edge tools and resources. However, the article also acknowledges the complex challenges that come with the adoption and implementation of cloud-based solutions, such as data security and privacy concerns, and the high costs associated with transitioning to these technologies. Despite these challenges, the article concludes that the advantages of these transformative technologies far outweigh the obstacles and that they offer unprecedented opportunities to transform research practices, spark innovation, and catalyze groundbreaking discoveries